Analysis of Determinant of Life Expectancy in East Java Province - Nurnas Kavila Elnung; Yozi Aulia Rahman (Economics Development Analysis Journal, 2019)
Economic development in East Java Province increases each year, can be seen from the Gross Regional Domestic Product (GRDP) Per Capita is increasing. The increase in GRDP Per Capita, cigarette consumption can increase so that the impact on tax receipts and an increase in life expectancy is low. Tax receipts made as the Province of East Java with revenue sharing fund of tobacco products excise highest. The purpose of this study was to analyze the influence of revenue sharing fund of tobacco products excise, betel leaves and tobacco expenditures and GRDP Per capita against life expectancy in East Java Province. Research methods used in this research is quantitative research methods with processing and data analysis technique used is Panel regression analysis with Fixed Effects Model (FEM). The results showed that only the GRDP Per Capita affects life expectancy while revenue sharing fund of tobacco products excise and expenditure of tobacco and betel leaves don't effect on life expectancy in East Java province. Based on those results, so in an attempt to improve life expectancy in East Java province by improving the use of programme revenue sharing fund of tobacco products excise that can provide direct benefits to society such as examination health routine.